ANALYSIS OF CONTINUE USAGE INTENTION OF BLU BCA DIGITAL IN JAKARTA - Halim, Jonathan Saputra; Iddo Daely, Axel Try; Trubus Andy Hartono, Samuel Septian (LPPM STIE Muhammadiah Bandung, 2023)
Blu BCA is one of an example of Digital Banking service owned by PT BCA Digital, which was developed to make it easier for customers to make financial transactions online. This study integrates perceived risk and perceived usefulness into UTAUT theoretical model to address this gap by using empirical research used a non-probability sampling method. A total of 200 respondents from user Blu BCA where they have used Blu BCA for at least 3 months. The study reveals that Social Influences, Facilitating Condition, and Perceived Usefulness influences Continuous Usage Intention whereas Perceived Risk is not influences Continuous Usage Intention